PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA KEPALA SEKOLAH TERHADAP KOMPETENSI PROFESIONAL GURU IPA SMP DI KABUPATEN SORONG SELATAN - Korwam, Yohana Adriana; Rumahorbo, Basa T. (Jurnal Ilmu Pendidikan Indonesia, 2016)
This Penelitain focusedly study the leadership influence and motivate the headmaster job to interest professional learn the IPA SMP. This Pelaksanaa Research [in] [doing/conducting][at] teacher SMP [in] 3 canton (Saifi, Seremuk And Teminabuan) amounting to 16 people learn the IPA. This Research have the character of descriptive and verikatif. To test the double regresi result of this research[is]menunjukan that there are contribution which signifikan [of] [among/between] leadership and motivate the job of headmaster of interest professional learn the IPA 76,5% and test the simple regresi result of research menunjukan that, leadership have an effect on the terhadapa of interest professional learn the high IPA SMP equal to 70,4%. [For a] while for the variable of motivate the headmaster job to interest professional learn the IPA obtained [by]result74,4%. Pursuant to this research earn the disimpulakan that there is influence by simultan [among/between] leadership and motivate the headmaster job to interest professional learn the IPA SMP [in] Regency Shove The South Arch Keywords: Leadership, Motiasi work the headmaster and Interest professional Learn the IPA